Φως ιλαρόν: From the various settings through the history of ecclesiastical chant to the latest composition by Prof. Gregorios Stathis - Mazera, Sevi (Journal of the International Society for Orthodox Music, 2020)
Vespers is the first service of the day. The liturgical books prescribe the order and the poetic text of the vesperal hymns. The musical codices called Papadikes, covering the cycle of offices, put in order the hymns of the Great Vespers “Composed by various poets”. The main function of the Vesper service as expressed in its prayers and its fixed psalmic parts are the praise of God for the end of the day and prayers for the night. One of the basic hymns of the Vespers is Φως ιλαρόν, is chanted at the entrance of the priest. The way the hymn is described in the manuscripts includes some of its general characteristics: “old poem”, “anonymous author”, “epilychnios hymn”, “epilychnios thanksgiving.” The designations “an ancient melos” or “very ancient” recorded in much of the religious and historical literature summarize the general acceptance of the hymn’s ancient origins.